1991
DOI: 10.1101/gad.5.10.1813
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulatory sequences in the lin-14 3'-untranslated region are necessary to generate a temporal switch during Caenorhabditis elegans development.

Abstract: The heterochronic gene lin-14 controls the temporal sequence of developmental events in the Caenorhabditis elegans postembryonic cell lineage. It encodes a nuclear protein that normally is present in most somatic cells of late embryos and L1 larvae but is absent at later stages. Two lin-14 gain-of-function mutations delete 3'-untranslated sequences causing an inappropriately high level of the lin-14 nuclear protein late in development. These mutations identify a negative regulatory element that controls the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 33 publications
4
115
0
7
Order By: Relevance
“…2B). To ask whether the desilencing of lin-14 upon inactivation of hmgs-1 is due to reduced lin-4 miRNA repression of lin-14 via its 3′ untranslated region (3′ UTR), we analyzed the down-regulation of lin-14 in the lin-14(n355) gain-of-function mutant, which lacks all of the sites in the lin-14 3′ UTR that are complementary to lin-4 and let-7 and its paralogs (23,24). lin-14 is not further desilenced when hmgs-1 is inactivated in the lin-14(n355) mutant background (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2B). To ask whether the desilencing of lin-14 upon inactivation of hmgs-1 is due to reduced lin-4 miRNA repression of lin-14 via its 3′ untranslated region (3′ UTR), we analyzed the down-regulation of lin-14 in the lin-14(n355) gain-of-function mutant, which lacks all of the sites in the lin-14 3′ UTR that are complementary to lin-4 and let-7 and its paralogs (23,24). lin-14 is not further desilenced when hmgs-1 is inactivated in the lin-14(n355) mutant background (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After more than a decade of research, it was determined that lin-4 did not code for a protein, but rather a small RNA species with imperfect complementarity to several sites in the 3Ј untranslated region (UTR) of lin-14 (Lee et al 1993). Because expression of lin-4 led to a decrease in lin-14 protein level without a decrease in mRNA level, this phenomenon was dubbed translational repression (Wightman et al 1991(Wightman et al , 1993. Biochemical analysis revealed that the repressed mRNAs remain in polysomes, suggesting that the block in expression occurs after translation initiation, although little is known about the mechanism (Olsen and Ambros 1999;Seggerson et al 2002).…”
mentioning
confidence: 99%
“…Most genes identified from mutagenesis screens are protein-coding, but lin-4 encodes a 22-nucleotide non-coding RNA that is partially complementary to 7 conserved sites located in the 3′-untranslated region (UTR) of the lin-14 gene (FIG. 1b) 13,14 . lin-14 encodes a nuclear protein, downregulation of which at the end of the first larval stage initiates the developmental progression into the second larval stage 13,15 .…”
Section: The Discovery Of Mirnasmentioning
confidence: 99%